Prototype Planning and Technician Job Report System at PT Visionet Data Internasional - Arief Herdiansah; Nora Fitriawati; Erni Rahmawati (Universitas Raharja, 2020)
PT Visionet Data International is a subsidiary of PT. Multipolar tbk, based in lippo Cyber ​​Park, and is engaged in outsourcing IT service providers, serving data center operational services and a company's daily IT operational services (IT Help desk). As a company engaged in services, PT Visionet Data International always strives to run its projects optimally and always maintain the reliability and scalability of computerized infrastructure that supports the customer's main business activities. The prototype planning, control and technician report system is an information system for scheduling, monitoring and reporting the job of technicians in the customer. In this study, researchers conducted an analysis and design of a technician job report system at PT. Data International Data Tangerang. The research method used was interview, survey and literature study methods. The system design process uses UML and the application is developed using PHP. The results of this study are information systems that can improve the services provided by PT. Visionet International Data to customers.